The determinants of venture capital across Europe: evidence across countries - Félix, E. G. S.; Pires, C. P.; Gulamhussen, M. A. (Journal of Financial Services Research, 2013)
This article analyses the determinants of European venture capital activity. The main novelty of our work is in accounting for the idiosyncrasies of the European venture capital market. In particular, we investigate whether the size of the merger and acquisition market (M&A) is important in explaining venture capital. Moreover, our work is the first that analyses the impact of the degree of information asymmetry at the macro level, the direct impact of the level of entrepreneurial activity and the impact of the unemployment rate on venture capital activity. We use aggregate data from 23 European countries for the period 1998-2003 to estimate panel data models with fixed and random effects. Our results reveal that the size of the M&A market and the market-to-book ratio have a positive impact on venture capital activity whereas the unemployment rate influences the venture capital market negatively. These results highlight the importance of the exit environment and of the degree of asymmetric information for the venture capital market.